2020
DOI: 10.1002/anie.202004002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonding Catalyzed Ring‐Closing C−O/C−O Metathesis of Aliphatic Ethers over Ionic Liquid under Metal‐Free Conditions

Abstract: O-heterocycles have wide applications, and their efficient and green synthesis is very interesting. Herein, we report hydrogen-bonding catalyzed ring-closing metathesis of aliphatic ethers to O-heterocycles over ionic liquid (IL) catalyst under metal-and solvent-free conditions. The IL 1butylsulfonate-3-methylimidazolium trifluoromethanesulfonate ([SO 3 H-BMIm][OTf]) is discovered to show outstanding performance, better than the reported catalysts. An interface effect plays an important role in mediating the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 43 publications
(34 reference statements)
1
54
1
1
Order By: Relevance
“…According to our results and the previous report, [24–28,44] we proposed a possible mechanism involving carbocation and ethers as the intermediates and synergistically promoted effect of hydrogen bonding (Scheme 6). Initially, we thought that the activities may be significantly influenced by the acidities of the ionic liquids.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…According to our results and the previous report, [24–28,44] we proposed a possible mechanism involving carbocation and ethers as the intermediates and synergistically promoted effect of hydrogen bonding (Scheme 6). Initially, we thought that the activities may be significantly influenced by the acidities of the ionic liquids.…”
Section: Resultssupporting
confidence: 82%
“…And trifluoromethylsulfonate was also essential for the reaction after testing several anions. Moreover, Liu et al proved the hydrogen bonding effect between ionic liquids and ethers using NMR analysis and DFT calculation [44] . Therefore, we proposed cation and anion of the ionic liquids would synergistically catalyze the reaction in our developed system through the effect of hydrogen bonding based on the phenomena.…”
Section: Resultsmentioning
confidence: 83%
“…S4), suggesting its high stability under the experimental conditions (fig. S5) ( 30 , 34 ). Thus, the [HO-EtMIm][OTf] catalyst shows a superior waste balance with economy factors (E-factors; that is the mass ratio of waste/isolated product) down to 0.40, indicating that this method has promising application potential ( 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Basic IL 1-ethyl-3-methylimidazolium acetate ([EMIM][OAc]) could efficiently catalyze one-pot oxidative transformation of alcohols into esters by hydrogen bond ( 29 ). The imidazolium ILs functionalized with -SO 3 H could catalyze the ring-closing metathesis of aliphatic ethers through three strong hydrogen bonds ( 30 ). Obviously, the hydrogen bond interactions in IL systems play important roles in these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Interestingly,h owever,t his characteristic also endows HBs with the ability to facilitate activation of O À Hbonds,through forming strengthened HBs with other proton acceptors such as electric-rich heteroatoms and halogen ions. [4] Thedecreased electron cloud density near the proton nucleus might weaken OÀHbonds,thus enhancing the reactivity of hydroxyl groups.Recently,some explorative studies have been performed in utilizing HBs for promoting the conversion of inert hydroxyl substrates and guiding pathways in purpose.F or example,t he selective activation of the primary hydroxyl group in diol could be accomplished via forming OÀH•••O=SHBs with DMSO as aproton acceptor, which was in favor of the selective alkoxyl radical transformation, rather than occurring b-scission due to the unselective activation of both two hydroxyl groups. [5] Han et al [6] presented that the HBs between the alcohol hydroxyl groups and ionic liquid [EMIM]OAc could accelerate the rate-determining step of hydroxyl groups activation, thus significantly promoting the oxidative esterification of inert aliphatic alcohols.I nt he case of heterogeneous catalysis, researchers also found that the surface-grafted nitrogencontaining ligands on EPy/Pt/Al 2 O 3 catalyst could form HBs with specific hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%